2004
DOI: 10.1345/aph.1e042
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant Hypersensitivity Syndrome: Lymphocyte Toxicity Assay for the Confirmation of Diagnosis and Risk Assessment

Abstract: Although AHS is a rare event, it should be suspected in patients who develop unexplained systemic manifestations following exposure to aromatic antiepileptics. The potential of lamotrigine to cause AHS should be remembered when this drug is used in subjects who have developed AHS on exposure to phenobarbital and other first-line antiepileptic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 8 publications
1
31
0
4
Order By: Relevance
“…We have formerly reported manifestation of DRESS syndrome in a five-year-old girl from our center (17). Similar manifestations have been reported in pediatric patients due to carbamazepine and phenobarbital (18,19).…”
Section: Discussionsupporting
confidence: 80%
“…We have formerly reported manifestation of DRESS syndrome in a five-year-old girl from our center (17). Similar manifestations have been reported in pediatric patients due to carbamazepine and phenobarbital (18,19).…”
Section: Discussionsupporting
confidence: 80%
“…We established cytoprotectiv estrategies concerning the hepatotoxicity associated with carbamazepine therapy. The toxicity was investigated in hepatocytes induced by phenobarbital (CYP450 inducer), because of the probability that the intermediate areneoxides formed in biotransformation might be the causes of the toxicity (Bavdekar et al;Kalapos, 2002;Madden et al, 1996;Shear & Spielberg, 1988). The results of our study showed that oxidative stress was involved in hepatotoxicity induced by carbamazepine and its metabolites.…”
Section: Discussionmentioning
confidence: 73%
“…In some investigations, it has been shown that reactive metabolites of carbamazepine could be involved in carbamazepineinduced hepatotoxicity. It is assumed that the accumulation of the arene oxide metabolites could be the responsible mechanism for the cellular damage caused by this drug (Bavdekar et al, 2004). Accumulation of arene oxide metabolite leads to direct mitochondrial toxicity, and also could result in immune response (Santos et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…For potent drugs, when only a small fraction of the adult dose is required for children, it becomes very easy to cause dosing errors of 10-fold or greater because of miscalculation or misplacement of the decimal point. For example, Selbst et al (35) reported a case of a 10-monthold baby who had received 10 times the correct dose of intravenous theophylline as a result of miscalculation of the drug dosage. Furthermore, incorrect recording of patients' weights and the difficulties health-care professionals have in making arithmetical calculations could also contribute to incorrect dosing (35).…”
Section: Increased Risk Of Medication Errors In Childrenmentioning
confidence: 99%
“…AHS has also been reported in a child treated with lamotrigine, a nonaromatic anti-epileptic (34). Also, cross-reactivity between aromatic antiepileptics and lamotrigine has been documented by doing the in vitro lymphocyte toxicity assay in an 11-year-old girl who developed AHS following administration of phenobarbital (35).…”
Section: Anti-epileptic Medicinesmentioning
confidence: 99%